Endogenous peripheral oxytocin measures can give insight into the dynamics of social relationships: a review - Crockford, Catherine; Deschner, Tobias; Ziegler, Toni E.; Wittig, Roman M. (Frontiers in Behavioral Neuroscience, 2014)
The neuropeptide, oxytocin, receives increasing attention due to its role in stress regulation and promoting affiliative social behavior. Research across mammals points to a complex pattern whereby social context and individual differences moderate the endogenous release of oxytocin as well as moderate the effects that exogenous administration of oxytocin has on social behavior. In addition to measuring central release of oxytocin or exogenous administration of oxytocin on social behavior, for example via inhalation, it is becoming evident that measuring endogenous peripheral oxytocin levels is an additional, informative tool. This is particularly so when oxytocin can be measured from non-invasively collected samples, such as in urine. Although it is still debated as to whether peripheral measures of oxytocin relate to central measures of oxytocin, anatomical and functional evidence indicate a link between the two. We argue that non-invasive measures of peripheral oxytocin hold several research and potential therapeutic advantages. Principally, study subjects can be sampled repeatedly in different social contexts where social history between interaction partners can be taken into account. Several hormones can be measured simultaneously allowing examination of the influence of oxytocin interactions with other hormones on motivational states. Valence of relationships as well as changes in relationship quality over time can be measured through endocrine responses. Also, the approach of identifying natural social contexts that are associated with endogenous oxytocin release offers the potential of behavioral therapy as an addition or alternative to chemical therapy in the field of mental health.